2019
DOI: 10.1007/s40273-019-00851-z
|View full text |Cite
|
Sign up to set email alerts
|

Fluocinolone Acetonide Intravitreal Implant for Treating Recurrent Non-infectious Uveitis: An Evidence Review Group Perspective of a NICE Single Technology Appraisal

Abstract: The National Institute for Health and Care Excellence (NICE) invited Alimera Sciences, the company manufacturing fluocinolone acetonide intravitreal implant (FAc) 0.19 mg (tradename ILUVIEN ®), to submit evidence on the clinical and costeffectiveness of FAc for treating recurrent non-infectious uveitis. Kleijnen Systematic Reviews Ltd, in collaboration with Maastricht University Medical Centre + , was commissioned to act as the independent Evidence Review Group (ERG). This paper contains a summary of the clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 6 publications
2
5
0
Order By: Relevance
“…We hypothesize that the purely inflammatory nature of uveitic macular edema responds better to intravitreal corticosteroids than DME, where other molecular pathways unrelated to inflammatory cytokines are involved. This study may come in support of cost-effectiveness analyses of FAc implant in NIU-PS [16]. No concerning IOPrelated adverse event was observed through the follow-up period.…”
Section: Discussionsupporting
confidence: 79%
“…We hypothesize that the purely inflammatory nature of uveitic macular edema responds better to intravitreal corticosteroids than DME, where other molecular pathways unrelated to inflammatory cytokines are involved. This study may come in support of cost-effectiveness analyses of FAc implant in NIU-PS [16]. No concerning IOPrelated adverse event was observed through the follow-up period.…”
Section: Discussionsupporting
confidence: 79%
“…Our results show the efficacy of FAc implant in the management of vascular leakage, CMO and retinal dysfunction, as previously reported [25][26][27][28]. In our study, baseline full-field ERGs showed a high incidence of generalised cone system dysfunction, consistent with previous studies, [9,10,18] with additional inner retinal rod system dysfunction in a minority.…”
Section: Discussionsupporting
confidence: 92%
“…The therapeutic role of local ocular corticosteroids in non-infectious posterior uveitis is well established [19][20][21][22][23][24][25][26][27]. Slow-release, sustained-delivery intravitreal corticosteroid implants are approved for non-infectious uveitis, including the FAc 0.19 mg intravitreal implant (Iluvien®; Alimera Sciences Limited, Aldershot, UK).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the treatment of the posterior uveitis, intravitreal injections of corticoids are used (triamcinolone acetonide and dexamethasone phosphate). Furthermore, there are two fluocinolone acetonide intravitreal implants, and a biodegradable dexamethasone drug delivery system of poly(lactic-co-glycolic acid) (PLGA) approved [140][141][142]. As a biological therapy, efalizumab, a humanized monoclonal antibody against CD11, is used in a complication of the posterior uveitis, the macular edema.…”
Section: Uveitismentioning
confidence: 99%